COMPARATIVE STUDIES OF JUVENILE HORMONE III IN OUTDOOR AND INDOOR REARED TASAR SILKWORM, Antheraea mylitta D. - G. SHIVA KUMAR; G. SHAMITHA (International Journal of Pharma and Bio Sciences, 2013)
The Tasar silkworm, Antheraea mylitta Drury (Daba TV), is an important wild, sericigenous insect and is commercially exploited in the nine states of tropical India. It encounters the vagaries of nature, pests and predators resulting in low crop yield. Rearing being outdoors, there is no control over the natural vagaries leading to irregular hatching of eggs and prolonged larval period. Not only the climatic hazards, its indefinite period of diapause leading to erratic moth emergence followed by inadequate seed support and other grainage problems also lead to severe crop loss. In order to overcome these difficulties, the concept of indoor rearing has been adopted. In the present investigation, a comparative analysis of Juvenile hormone (control larval period) extracted from the haemolymph of outdoor and indoor reared fifth instar 10th day larvae of tasar silkworm has been taken up. The studies has revealed that JH III levels decreased in indoor reared worms in the second and third crops when compared to that of the outdoor reared ones.